All Nearest Neighbors Query including Scores Road Network - Kim, Hyo Kyun; Chung, Tae Sun (Proceedings - 2020 International Conference on Computational Science and Computational Intelligence, CSCI 2020, 2020)
This paper introduces an improved ANN (All Nearest Neighbor) algorithm using the SCL (Standard Clustered Loop) algorithm to reduce the consumption of computing resources that can occur when searching for the data object nearest to the query object in the process of executing the algorithm. Additionally, a method to improve ANN algorithm is proposed. When the algorithm is executed, it is a situation in which the user finds a data object adjacent to the user. In this case, our technique applies the criteria set provided by users.
Keywords: All nearest neighbors; ANN algorithm; Computing resource; Data objects; Query object; Road network; ANN; nearest neighbor; road network